2009
DOI: 10.1086/593124
|View full text |Cite
|
Sign up to set email alerts
|

Study of Blood Contact in Simulated Surgical Needlestick Injuries With Single or Double Latex Gloving

Abstract: The results revealed that double gloving leads to a significant reduction in the quantity of blood transferred during needlestick injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
(10 reference statements)
0
24
0
3
Order By: Relevance
“…It is emphasized that in emergency situations, HCPs need to be more careful. 5,8 According to a study, 31 double gloving provides a significant reduction in the quantity of blood transferred during a needlestick injury. Double gloving offers considerable protection against exposure to contaminants in the blood and body fluids of the patient and should be made routine, especially in developing countries where HIV, hepatitis B and C are widely prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that in emergency situations, HCPs need to be more careful. 5,8 According to a study, 31 double gloving provides a significant reduction in the quantity of blood transferred during a needlestick injury. Double gloving offers considerable protection against exposure to contaminants in the blood and body fluids of the patient and should be made routine, especially in developing countries where HIV, hepatitis B and C are widely prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…A range of studies, including randomized trials, have shown that perforations develop in surgical gloves during a wide range of procedures and that double gloving reduces exposure to blood and other bodily fluids. [6][7][8][9][10][11] These data were analyzed in a Cochrane meta-analysis by Mischke and Verbeek, 12 who examined 12 studies showing a statistically significant benefit of double gloving to reduce perforations of a surgeon's innermost glove. The American College of Surgeons supports double gloving as a routine safety practice in its Statement on Sharps Safety.…”
mentioning
confidence: 99%
“…For example, the volume of inoculum through a single layer of latex is approximately 0.064 microL, compared with 0.011 microL through 2 layers, which is a nearly 6-fold decrease. 5558 Furthermore, double-gloving can be used to alert the surgeon to glove failure. 59 Surgeons are often unaware of glove perforations, particularly minute perforations, which can be detected with double-gloving.…”
Section: Strategies For Preventionmentioning
confidence: 99%